2019
DOI: 10.1002/jbm.a.36713
|View full text |Cite
|
Sign up to set email alerts
|

Dodecenylsuccinic anhydride modified collagen hydrogels loaded with simvastatin as skin wound dressings

Abstract: Skin wound healing presents a unique challenge because of its complex healing process. Herein, we developed a hydrophobic wound dressing to incorporate simvastatin, which has potential application in the treatment of ulcers and prevention of wound infection. For that matter, collagen hydrogels were grafted with dodecenylsuccinic anhydride (DDSA). The chemical modification was confirmed by FTIR and solid state 13C‐NMR spectroscopies while the ultrastructure was observed by scanning electron microscope (SEM) ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 70 publications
0
13
0
Order By: Relevance
“…e antimicrobial activity was stronger against S. aureus. Also, collagen hydrogels provided a prolonged antibacterial activity when they involved simvastatin, and findings revealed that these materials could stimulate macrophages which is useful in wound healing processes [26]. e MTT assay of Chakrabarti et al study showed that bFGF and collagen matrix hydrogel had minimal toxicity on the L929 mouse fibroblast cell line, did not inhibit cell proliferation, and could be further investigated in burn wounds [27].…”
Section: Discussionmentioning
confidence: 99%
“…e antimicrobial activity was stronger against S. aureus. Also, collagen hydrogels provided a prolonged antibacterial activity when they involved simvastatin, and findings revealed that these materials could stimulate macrophages which is useful in wound healing processes [26]. e MTT assay of Chakrabarti et al study showed that bFGF and collagen matrix hydrogel had minimal toxicity on the L929 mouse fibroblast cell line, did not inhibit cell proliferation, and could be further investigated in burn wounds [27].…”
Section: Discussionmentioning
confidence: 99%
“…When used as the basic component of wound dressings, it has weak antigenicity, promotes cell growth and proliferation, promotes coagulation and avoids scar formation, etc. [ 81 ]. Col-HA hydrogels prepared by HRP covalent cross-linking not only showed good biocompatibility and biodegradability but also spontaneously promoted angiogenesis and played a positive role in the formation of epithelium and collagen fiber [ 82 ].…”
Section: Biomaterials For Preparing Hydrogelsmentioning
confidence: 99%
“…Simvastatin showed antimicrobial and anti-inflammatory properties in 2009 which make them promising for cutaneous wound cure. DDSA collagen hydrogels have exhibited better mechanical properties and lower degradation levels and the potential for waterinsoluble drugs to act as drug carriers 4 . Skin replacements are one of the major skin loss remedies, and the best treatment choice would be a skin replacement which is readily available.…”
Section: Collagenmentioning
confidence: 99%
“…Skin is a highly vascularized, bio mineralized composite material composed of fibroblasts and collagen surrounded by specialized extracellular matrix with high mechanical strength and structural complexity. [1][2][3][4] Skin tissue defects have become one of the major sources of mortality and morbidity among all age group people worldwide. Although the auto grafts and allograft were regarded as the high attainment for wound repair, the approach was limited because of their unwanted effects (i.e.…”
Section: Introductionmentioning
confidence: 99%